HUBUNGAN KECEMASAN IBU DENGAN KECEMASAN ANAK SAAT HOSPITALISASI ANAK - Febriana Sartika Sari; Madya Sulisno (Jurnal Keperawatan Diponegoro, 2012)
The prevalence of hospitalized child’s anxiety reached 75%. The anxiety worsen  the healing process of diseases. The hypothesis of the relationship between mother’s anxiety and child’s anxiety was emerged because many mothers had anxiety in child’s hospitalization. The mothers were depressed, confused, or  very angry in child’s hospitalization. The research aimed to find out the relationship between the level of Mother’s anxiety and the level of  3-year-old to 6-year-old child’s anxiety who had hospitalization in Room Anggrek Ambarawa Public Hospital. Researcher also aimed to identify the level of mother’s and child’s anxiety acc ording to the their characteristics. The research used non experimental quantitative method and correlation study design. The data were collected by interview using questioner. The sample were 60 partners of mother and child who were taken by incidental sampling technique. The data were analyzed using kendalls tau formula. The research indicated that the occurance of mothers and children with mild anxiety was 63.3%, the occurance of mothers with mild anxiety and children with moderate anxiety was 10%, the occurance of mothers with moderate anxiety and children with mild anxiety was 5%, and the occurance of mothers and children with moderate anxiety was 21.67%. Kendalls tau correlation test indicated that p value is 0.000 and coefficient correlation is 0.643. The conclusion was there is relationship between the level of Mother’s anxiety and the level of  3-year-old to 6-year-old child’s anxiety who had hospitalization in Room Anggrek Ambarawa Public Hospital. The level of mother’s and child’s anxiety were different according to the characteristics.  The author recommended that nurse should give comprehensive nursing care and the hospital should make Standart Operating Procedure for anxiety management